Efektivitas Terapi Latihan Fisik Terhadap Peningkatn Range Of Motion Pada Pasien Cedera Anterior Cruciate Ligament - Yulius Agung Saputro; Aditya Rachman (CV Putra Publisher, 2023)
In general, sports cannot avoid injuries, injuries can occur due to internal and external factors. One of the most common injuries is injury to the ligament, for example the anterior cruciate ligament (ACL) for which anterior cruciate ligament injury is the focus for rehabilitation programs, therefore how much benefit of physical exercise therapy to increase the range of motion.This study aims to determine the effectiveness of physical exercise therapy to increase the range of motion in patients with anterior cruciate ligament injuries at the Jogja Orthopedic sport clinic. The research method used in this study was a quasi-experimental method using a one group pretest-posttest design. Quasi-research is research with a quantitative approach in this study using the independent variable, namely physical exercise therapy and vice versa, the dependent variable, namely increasing the range of motion. The patient population in this study was 16 people. The sample in this study used a purposive sampling technique with the criteria that the patient was still in phase 1 after anterior cruciate ligament reconstruction. The research instrument used a goniometer to measure the scope of the knee joint, namely flexion and extension. Data analysis technique with the T-test through the prerequisite analysis test for normality test with Shapiro Wilk and homogeneity test. The results of the study showed (1) the effectiveness of increasing the range of motion in flexion movements by 0.261% and extension movements by 0.739%, with a significant value of 0.095 > 0.05. Based on these results, it can be concluded that physical exercise therapy is effective for increasing the Range of Motion in anterior cruciate ligament injuries. (2) physical therapy has the effect of accelerating the process of increasing the range of motion.